Gallium nitride carbon layer coated porous silicon negative electrode material, preparation method and application thereof
By coating porous silicon material with gallium nitride carbon layer, the problem of insufficient volume expansion and conductivity of silicon negative electrode materials in lithium-ion batteries is solved, the cycle stability of the battery and lithium-ion storage performance are improved, and more efficient electricity Chemical properties.
Patent Information
- Application Number
- CN202411453986.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-03
AI Technical Summary
The silicon negative electrode material is broken and SEI film ruptured due to volume expansion in lithium-ion batteries, which affects the first Coulomb efficiency and cycle life of the battery, and has insufficient electrical conductivity, limiting its application.
The gallium nitride carbon layer is used to coat the porous silicon material. By forming a dense gallium nitride layer and carbon layer outside the porous silicon, the interface phase of the fast ion conductor Li3N and the fast electronic conductor Li-Ga alloy is formed to jointly improve the interface lithium ion/ Electronic conductivity and electrode/electrolyte interface stability.
It effectively alleviates the volume expansion of silicon, enhances the cycle stability and safety of the battery, improves the lithium-ion storage performance, and is simple in preparation and low in energy consumption, which is suitable for large-scale industrial production.
Smart Images

Figure CN119252901A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion battery materials, and in particular relates to a gallium nitride carbon layer-coated porous silicon negative electrode material, a preparation method and an application thereof. Background Art
[0002] Lithium-ion batteries are widely used in electric vehicles, consumer electronics, energy storage, aerospace, military and security fields due to their high energy density, long life and fast charging capability. Silicon (Si) has a high theoretical specific capacity (4200mAhg −1 ), and is regarded as a very promising negative electrode material for high energy density lithium-ion batteries. However, there are many problems in the application of silicon negative electrode materials in lithium-ion batteries. The main problem of silicon negative electrode is that it will undergo significant volume expansion (up to 300%) during the charge and discharge process, which will cause silicon particles to break and SEI (Solid electrolyte interphase) film to rupture and thicken, thereby affecting the first coulomb efficiency and cycle life of the battery. In addition, the poor conductivity of silicon materials also limits its application in lithium-ion batteries. In response to the above-mentioned problems faced by silicon negative electrodes, especially the large volume change and low conductivity of silicon, a series of structural designs and composite improvements have been made to silicon to improve the electrochemical performance of silicon negative electrode materials. For example, silicon nanoparticles, silicon nanowires, silicon nanotubes, silicon nanosheets, and porous secondary structures assembled from these nanounits, etc., due to the large specific surface area brought by the size of nanoparticles and the available free space around them, provide more lithium ion reaction sites, shorten the migration path of lithium ions, and provide the space required for silicon to expand in volume, thereby improving the rate performance and cycle stability of silicon negative electrode batteries. On this basis, it is also necessary to further improve its electrochemical stability by combining the advantages brought by structural design and the advantages of other composite materials. Among them, designing a thin and strong interfacial functional layer is one of the effective strategies to inhibit side reactions between silicon and liquid electrolytes. The SEI film is often formatted and destroyed repeatedly, consuming more lithium and producing inactive and low-conductivity substances. Therefore, the required silicon anode material should not only have a low volume change during the cycle, but also have a strong SEI film during the cycle.
[0003] At present, people have proposed different methods to improve the stability of the interface. For example, modifying the surface of silicon particles by coating with a carbon layer is one of the most feasible options because it has high electronic conductivity and helps to form a stable SEI film. However, the effect is limited because the silicon and carbon layers are in close contact and there is not enough space to accommodate the volume expansion of silicon. Once the volume expansion of silicon exceeds the elastic limit of the carbon layer or there are defects in the carbon layer, the core-shell structure is easily destroyed and cannot adapt to long-term cycles.
[0004] The formation of SEI film on silicon-based negative electrode has an important influence on the performance and life of lithium-ion batteries. On the one hand, it can slow down the volume expansion of silicon-based negative electrode during the cycle, thereby extending the battery life. On the other hand, the formation of SEI film can also improve the stability and safety of the battery and reduce the risk of internal short circuit and thermal runaway of the battery. Therefore, SEI film is of great significance in the research and application of lithium-ion batteries. Summary of the invention
[0005] In view of the deficiencies of the above-mentioned prior art, the present invention provides a gallium nitride carbon layer coated porous silicon negative electrode material, a preparation method and application thereof. The specific technical scheme is as follows: The first object of the present invention is to provide a method for preparing a gallium nitride carbon layer coated porous silicon negative electrode material, comprising the following steps: S1: placing citric acid and gallium nitrate in deionized water and stirring to obtain a gel solution; S2: placing porous silicon particles into the gel solution obtained in S1 and stirring to obtain a suspension, then heating the suspension to evaporate to dryness to obtain a porous silicon material coated with the complex; S3: The porous silicon material coated with the complex obtained in S2 is placed in a tubular furnace, and subjected to nitridation treatment in an ammonia atmosphere. After two-stage heat preservation, the porous silicon material is cooled to room temperature and taken out to obtain a porous silicon negative electrode material coated with a gallium nitride carbon layer.
[0006] The present invention obtains a core-shell structured gallium nitride carbon layer-coated porous silicon composite material by coating the outside of porous silicon with a gallium nitride carbon layer. The composite material constructs an ideal artificial SEI at the interface of the porous silicon negative electrode, and its outer layer has a dense gallium nitride layer and a carbon layer. Gallium nitride produces lithium nitride, gallium and lithium-gallium alloy, a mixed ion / electronic interface layer of a fast ion conductor Li3N phase and a fast electron conductor Li-Ga alloy interface phase during the cycle process. The lithium ion / electron conductivity of the interface and the enhanced electrode / electrolyte interface stability are improved through the synergistic effect of the two to improve the lithium ion storage performance. The preparation method of the present invention is simple, low in energy consumption and low in cost, and can be suitable for large-scale industrial production.
[0007] Furthermore, in S1, the molar ratio of citric acid to gallium nitrate is 1:(0.5-10); preferably 1:(0.7-5); further preferably 1:(1-2); more preferably 1:1.
[0008] The present invention directly affects the capacity and cycle stability of the porous silicon negative electrode material by controlling the ratio of citric acid to gallium nitrate. If the citric acid content is too low, the complexation cannot be complete, and the porous silicon negative electrode material uniformly coated with gallium nitride cannot be obtained; if the citric acid content is too high, the final coated carbon layer is too thick, resulting in adhesion of the porous silicon. Therefore, it is extremely important to control the ratio of citric acid to gallium nitrate powder in the present invention.
[0009] Furthermore, in S1, the temperature of the deionized water is 70-90° C., and the stirring time is 1-14 h.
[0010] Furthermore, in S2, the porous silicon particle size is 1-10 μm; more preferably 3-5 μm; and more preferably 3 μm.
[0011] Furthermore, in the S2, the mass ratio of the porous silicon to the gallium nitrate in the S1 is (20-1):1, more preferably (10-2):1, and more preferably 2.5:1.
[0012] Furthermore, in S2, the stirring time is 1 to 24 hours; more preferably 2 to 12 hours; more preferably 6 hours; and the temperature of heating to dryness is 90 to 110°C.
[0013] The present invention is very important in selecting the size of porous silicon, the proportion of porous silicon and the stirring time. If the porous silicon particle size is too large, the subsequent lithium insertion is incomplete, which reduces the initial coulombic efficiency; if the porous silicon particle size is too small, it will cause agglomeration, increase side reactions, aggravate the volume effect and other problems. If the proportion of porous silicon is too small, the coating layer of the prepared material is too thick, and the particles are easy to agglomerate, affecting the capacity and cycle stability; if the proportion of porous silicon is too high, the improvement of the prepared material is not obvious. If the stirring time is too short, the coating of the prepared material is uneven, which reduces the electrochemical performance of the final material.
[0014] Furthermore, in S3, the heating rate of the nitriding treatment is 0.1-20°C / min; preferably 2-10°C / min; further preferably 5-10°C / min; more preferably 5°C / min.
[0015] Further, in S3, the temperature of the first section of the two-stage insulation is 100~600℃, and the insulation time is 10~180min; the temperature of the second section is 700~1000℃, and the insulation time is 120~360min; preferably, the temperature of the first section is 200~400℃, and the insulation time is 30~120min, and the temperature of the second section is 800~900℃, and the insulation time is 150~300min; more preferably, the temperature of the first section is 300℃, and the insulation time is 60min, and the temperature of the second section is 900℃ and the insulation time is 240min.
[0016] The selection of heating rate, heating temperature and holding time is very important in the present invention. If the heating rate is too fast, the gallium nitride carbon layer coating will have more pores and loose structure, and will break due to the huge volume expansion of silicon during the lithium insertion and extraction process; if the heating rate is too slow, the gallium nitride carbon layer coating will have a dense structure, which is not conducive to the migration of lithium ions; if the heating temperature is too low or the holding time is too short, it will lead to incomplete nitridation and the presence of gallium oxide on the surface of the prepared material. When the heating temperature is low, even if the holding time is extended, porous silicon coated with a uniform gallium nitride carbon layer cannot be obtained; if the heating temperature is too high or the holding time is too long, the thickness of the gallium nitride carbon layer coating on the surface cannot be controlled, thereby reducing the electrochemical properties of the material.
[0017] The second object of the present invention is to provide a gallium nitride carbon layer coated porous silicon negative electrode material, which is prepared by the above-mentioned preparation method.
[0018] The third object of the present invention is to provide a lithium-ion battery, comprising the above-mentioned gallium nitride carbon layer-coated porous silicon negative electrode material.
[0019] The beneficial effects of the present invention are: The present invention obtains a gallium nitride carbon layer-coated porous silicon material at low temperature (below 1200°C) by strictly controlling the reaction conditions, specific ratio of mixing materials and nitriding treatment, and is used as a negative electrode material for lithium-ion batteries, effectively improving the problem of insufficient silicon conductivity and alleviating the huge volume expansion caused by silicon deintercalation and lithium extraction; at the same time, gallium nitride produces a mixed ion / electronic interface layer of lithium nitride, gallium and lithium-gallium alloy, fast ion conductor Li3N phase and fast electron conductor Li-Ga alloy interface phase during the cycle process, and improves the lithium ion storage performance by improving the interface lithium ion / electronic conductivity and enhanced electrode / electrolyte interface stability through the synergistic effect of the two; liquid metal gallium can play a role in repairing the surface microcracks generated by silicon during the process of lithium ion extraction and extraction, thereby improving the cycle stability of the battery. Moreover, the preparation method of the present invention is simple, has low energy consumption and low cost, and can be applied to large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a SEM image of the gallium nitride carbon layer coated porous silicon (p-Si@GaN) of Example 1 of the present invention; Figure 2 This is an XRD diagram of the gallium nitride carbon layer coated porous silicon (p-Si@GaN) according to Example 1 of the present invention; Figure 3 This is the EDS element spectrum of p-Si@GaN in Example 1 of the present invention; Figure 4 This is the first charge and discharge curve of p-Si@GaN in Example 1 of the present invention; Figure 5This is a graph of electrochemical cycle performance of p-Si@GaN and raw material porous silicon (p-Si) according to Example 1 of the present invention; Figure 6 This is a comparison diagram of the impedance before and after cycling of p-Si@GaN and raw material porous silicon (p-Si) in Example 1 of the present invention; Figure 7 This is the electrochemical cycle performance diagram of p-Si-2 of Comparative Example 1 of the present invention; Figure 8 This is the electrochemical cycle performance diagram of p-Si-3 of Comparative Example 2 of the present invention; Fig. 9 This is the electrochemical cycle performance diagram of p-Si-4 of Comparative Example 3 of the present invention; Fig.10 This is the electrochemical cycle performance diagram of p-Si-5 of comparative example 4 of the present invention. DETAILED DESCRIPTION
[0021] The principles and features of the present invention are described below in conjunction with embodiments. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention. Example
[0022] A method for preparing a gallium nitride carbon layer coated porous silicon negative electrode material comprises the following steps: (1) Pour citric acid and gallium nitrate powder in a molar ratio of 1:1 into 80°C deionized water and stir thoroughly for 12 hours to obtain a gel solution; (2) Porous silicon with a mass ratio of 2.5:1 to gallium nitrate and a particle size of 3 to 5 μm is poured into the gel solution formed in (1), and stirred for 6 hours to obtain a suspension. The suspension is then placed on a heating plate and heated and stirred at 100° C., and taken out after evaporation to obtain a porous silicon material coated with a complex. (3) The sample obtained in (2) was placed in a quartz crucible and heat treated in a tubular furnace into which ammonia gas was introduced at a flow rate of 120 L / min. The temperature in the tubular furnace was increased to 300°C at a heating rate of 5°C / min and kept at that temperature for 1 h. The temperature was then increased to 900°C at a heating rate of 5°C / min and kept at that temperature for 4 h. After the temperature was maintained at that temperature, the sample was cooled to room temperature and then taken out to obtain porous silicon coated with a gallium nitride carbon layer (denoted as p-Si@GaN).
[0023] Figure 1 The SEM image of the porous silicon material (p-Si@GaN) coated with a gallium nitride carbon layer shows that the porous silicon skeleton is clear and has three-dimensional connected pores, and the coating layer does not destroy the porous silicon morphology structure.
[0024] Figure 2This is the XRD pattern of the porous silicon material coated with gallium nitride carbon layer (p-Si@GaN). The broad diffraction peaks at 28.5°, 47.3°, 56.2°, 69.2°, 76.5° and 87.9° are assigned to the (111), (220), (311), (400), (331) and (442) planes of the Si cubic phase. The three broad diffraction peaks at 30°~40° correspond to GaN, and the wider and flatter peak at around 20° corresponds to amorphous carbon, indicating the successful preparation of gallium nitride and carbon without the generation of other impurities.
[0025] Figure 3 This is the EDS elemental spectrum of p-Si@GaN, which reveals that Ga and N are evenly distributed on Si, and no separate existence of GaN particles is observed, proving that gallium nitride is evenly coated on porous silicon. Gallium nitride and carbon layers can inhibit the volume expansion of silicon and reduce the occurrence of side reactions; in the subsequent lithium insertion process, the gallium nitride layer produces a mixed ion / electronic interface layer of lithium nitride, gallium, lithium-gallium alloy, fast ion conductor Li3N phase and fast electron conductor Li-Ga alloy interface phase during the cycle process, and improves the lithium ion storage performance through the synergistic effect of the two to improve the interface lithium ion / electron conductivity and enhance the electrode / electrolyte interface stability; liquid metal gallium can repair the surface microcracks generated by silicon during the process of lithium ion insertion and extraction, thereby improving the cycle stability of the battery.
[0026] Figure 4 The first charge and discharge curve of p-Si@GaN. The first coulomb efficiency of p-Si@GaN is 80.49% (the first coulomb efficiency of raw porous silicon p-Si is 81.16%). Since GaN undergoes an irreversible reaction to generate Li3N when it is first embedded with lithium, Li + It failed to be completely released, but the presence of the carbon layer improved the first coulombic efficiency, resulting in the first coulombic efficiency not decreasing too much compared with the raw porous silicon.
[0027] Figure 5 The figure is the electrochemical cycling performance diagram of p-Si@GaN and p-Si; after cycling for 3 cycles at a current density of 0.1 A / g and then cycling at a current density of 1A / g, p-Si@GaN still retains a reversible specific capacity of 1678.5 mAh / g after 150 cycles, and the capacity retention rate is 91.4% (calculated based on the discharge capacity of the fourth cycle at 1 A / g as the initial capacity); p-Si retains a reversible specific capacity of 1375.1 mAh / g after 150 cycles, and the capacity retention rate is 61.8%. Compared with p-Si, p-Si@GaN has a higher capacity retention rate and faster reaction kinetics.
[0028] Figure 6The impedance comparison diagram of p-Si@GaN and p-Si before and after cycling. Obviously, the R SEI The impedance value is smaller than that of the p-Si negative electrode, and it has a faster electron / ion interface transmission capability. In addition, after 1 cycle, we processed the Nyquist diagrams in the low-frequency region of the p-Si and p-Si@GaN negative electrodes, and their Z′ and ω −1 / 2 Linear fitting shows that the slope of p-Si is about 1.6 times that of p-Si@MgF2 negative electrode, that is, the lithium ion diffusion coefficient of p-Si@GaN negative electrode is about 2.6 times that of p-Si. This shows that p-Si@GaN negative electrode has more prominent kinetic characteristics in lithium ion storage.
[0029] A method for preparing a gallium nitride carbon layer coated porous silicon negative electrode material comprises the following steps: (1) Pour citric acid and gallium nitrate powder in a molar ratio of 3:1 into 80°C deionized water and stir thoroughly for 12 hours to obtain a gel solution; (2) Porous silicon with a mass ratio of 2.5:1 to gallium nitrate and a particle size of 3 to 5 μm is poured into the gel solution formed in (1), and stirred for 6 hours to obtain a suspension. The suspension is then placed on a heating plate and heated and stirred at 100° C., and taken out after evaporation to obtain a porous silicon material coated with a complex. (3) The sample obtained in (2) was placed in a quartz crucible and heat treated in a tubular furnace into which ammonia gas was introduced at a flow rate of 120 L / min. The temperature in the tubular furnace was increased to 300°C at a heating rate of 5°C / min and kept at that temperature for 1 h. The temperature was then increased to 900°C at a heating rate of 5°C / min and kept at that temperature for 4 h. After the temperature was maintained at that temperature, the sample was cooled to room temperature and then taken out to obtain porous silicon coated with a gallium nitride carbon layer (denoted as p-Si-2).
[0030] Figure 7 This is the electrochemical cycling performance diagram of p-Si-2 (the molar ratio of citric acid to gallium nitrate powder is 2:1), with an initial efficiency of 83.4%. At the same time, at a current density of 1A / g, the reversible specific capacity after 100 cycles is 1189.6mAh / g, and the capacity retention rate is 80.3%.
[0031] The citric acid content of this embodiment is relatively high. Since citric acid is the only carbon source in the embodiment, a too high content will cause the outer carbon coating layer on the surface of the material to be too thick and uneven, reducing the transmission efficiency of lithium ions and causing the subsequent generation of an uneven SEI layer, thereby adversely affecting the electrochemical properties of the material.
[0032] A method for preparing a gallium nitride carbon layer coated porous silicon negative electrode material comprises the following steps: (1) Pour citric acid and gallium nitrate powder in a molar ratio of 1:1 into 80°C deionized water and stir thoroughly for 12 hours to obtain a gel solution; (2) Porous silicon with a mass ratio of 1:2 to gallium nitrate and a particle size of 3 to 5 μm is poured into the gel solution formed in (1), and stirred for 6 hours to obtain a suspension. The suspension is then placed on a heating plate and heated and stirred at 100° C., and taken out after evaporation to obtain a porous silicon material coated with a complex. (3) The sample obtained in (2) was placed in a quartz crucible and heat treated in a tubular furnace into which ammonia gas was introduced at a flow rate of 120 L / min. The temperature in the tubular furnace was increased to 300°C at a heating rate of 5°C / min and kept at that temperature for 1 h. The temperature was then increased to 900°C at a heating rate of 5°C / min and kept at that temperature for 4 h. After the temperature was maintained at that temperature, the sample was cooled to room temperature and then taken out to obtain porous silicon coated with a gallium nitride carbon layer (denoted as p-Si-3).
[0033] Figure 8 This is the electrochemical cycling performance diagram of p-Si-3 (the mass ratio of porous silicon to gallium nitrate is 1:1), with an initial efficiency of 71.3%. At the same time, at a current density of 1A / g, the reversible specific capacity after 100 cycles is 628.9mAh / g, and the capacity retention rate is 61.8%.
[0034] In this embodiment, the gallium nitrate content is too high, resulting in a gallium nitride coating that is too thick and uneven. Due to the irreversible reaction of the first lithium insertion of gallium nitride, the initial coulombic efficiency is reduced, and an uneven SEI layer is subsequently generated, which has an adverse effect on the electrochemical properties of the material.
[0035] A method for preparing a gallium nitride carbon layer coated porous silicon negative electrode material comprises the following steps: (1) Pour citric acid and gallium nitrate powder in a molar ratio of 1:1 into 80°C deionized water and stir thoroughly for 12 hours to obtain a gel solution; (2) Selecting a porous silicon to gallium nitrate mass ratio of 2.5:1 and a porous silicon particle size of 3-5 μm, pouring the porous silicon into the gel solution formed in (1), stirring for 6 h, and obtaining a suspension, then placing the suspension on a heating plate and heating it at 100 °C with stirring, and taking it out after evaporation to obtain a complex-coated porous silicon material; (3) The sample obtained in (2) was placed in a quartz crucible and heat treated in a tubular furnace into which ammonia gas was introduced at a flow rate of 120 L / min. The temperature in the tubular furnace was increased to 300°C at a heating rate of 5°C / min and kept at that temperature for 1 h. The temperature was then increased to 600°C at a heating rate of 5°C / min and kept at that temperature for 1 h. After the temperature was maintained at that temperature, the sample was cooled to room temperature and then taken out to obtain porous silicon coated with a gallium nitride carbon layer (denoted as p-Si-4).
[0036] Fig. 9This is the electrochemical cycle performance diagram of p-Si-4 (600℃ and kept warm for 1h). Its first efficiency is 69.3%. At the same time, at a current density of 1A / g, the reversible specific capacity after 100 cycles is 1231.5mAh / g, and the capacity retention rate is 70.4%.
[0037] In this embodiment, the nitridation temperature is low and the time is short, and gallium nitride cannot be completely nitrided to form a large particle negative electrode material, and silicon has no porous morphology, which affects its electrochemical performance.
[0038] A method for preparing a gallium nitride carbon layer coated porous silicon negative electrode material comprises the following steps: (1) Pour citric acid and gallium nitrate powder in a molar ratio of 1:1 into 80°C deionized water and stir thoroughly for 12 hours to obtain a gel solution; (2) Porous silicon with a mass ratio of 2.5:1 to gallium nitrate and a particle size of 3 to 5 μm is poured into the gel solution formed in (1), and stirred for 6 hours to obtain a suspension. The suspension is then placed on a heating plate and heated and stirred at 100° C., and taken out after evaporation to obtain a porous silicon material coated with a complex. (3) The sample obtained in (2) was placed in a quartz crucible and heat treated in a tubular furnace into which argon gas was introduced at a flow rate of 120 L / min. The temperature in the tubular furnace was increased to 300°C at a heating rate of 5°C / min and kept at that temperature for 1 h. The temperature was then increased to 900°C at a heating rate of 5°C / min and kept at that temperature for 4 h. After the temperature was maintained at that temperature, the sample was cooled to room temperature and then taken out to obtain porous silicon coated with a gallium nitride carbon layer (denoted as p-Si-5).
[0039] Fig.10 This is the electrochemical cycle performance diagram of p-Si-5 (argon calcined), with an initial efficiency of 74.6%. At the same time, at a current density of 1A / g, the reversible specific capacity after 100 cycles is 1276.3mAh / g, and the capacity retention rate is 77.9%. This is because no nitrogen element is introduced during argon calcination, and a porous silicon material coated with a gallium nitride carbon layer cannot be formed, which makes it difficult for lithium ions to be deintercalated, affects the electrochemical performance, and has poor cycle performance.
[0040] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a gallium nitride carbon layer coated porous silicon negative electrode material, characterized in that: The steps include: S1: placing citric acid and gallium nitrate in deionized water and stirring to obtain a gel solution; S2: placing porous silicon particles into the gel solution obtained in S1 and stirring to obtain a suspension, then heating the suspension to evaporate to dryness to obtain a porous silicon material coated with the complex; S3: The porous silicon material coated with the complex obtained in S2 is placed in a tubular furnace, and subjected to nitridation treatment in an ammonia atmosphere. After two-stage heat preservation, the porous silicon material is cooled to room temperature and taken out to obtain a porous silicon negative electrode material coated with a gallium nitride carbon layer.
2. The method for preparing the gallium nitride carbon layer coated porous silicon negative electrode material according to claim 1, characterized in that: In S1, the molar ratio of citric acid to gallium nitrate is 1:(0.1-10).
3. The method for preparing the gallium nitride carbon layer coated porous silicon negative electrode material according to claim 1, characterized in that: Furthermore, in S1, the temperature of the deionized water is 70-90° C., and the stirring time is 1-14 h.
4. The method for preparing the gallium nitride carbon layer coated porous silicon negative electrode material according to claim 1, characterized in that: In S2, the porous silicon particle size is 1-10 μm.
5. The method for preparing the gallium nitride carbon layer coated porous silicon negative electrode material according to claim 1, characterized in that: In the S2, the mass ratio of the porous silicon to the gallium nitrate in the S1 is (30-1):
1.
6. The method for preparing the gallium nitride carbon layer coated porous silicon negative electrode material according to claim 1, characterized in that: In S2, the stirring time is 1-24 hours; and the heating and evaporation temperature is 90-110°C.
7. The method for preparing the gallium nitride carbon layer coated porous silicon negative electrode material according to claim 1, characterized in that: In S3, the heating rate of the nitriding treatment is 0.1-20°C / min.
8. The method for preparing the gallium nitride carbon layer coated porous silicon negative electrode material according to claim 1, characterized in that: In S3, the temperature of the first stage of the two-stage insulation is 100-600° C., and the insulation time is 10-180 min; the temperature of the second stage is 700-1000° C., and the insulation time is 120-360 min.
9. A gallium nitride carbon layer coated porous silicon negative electrode material, characterized in that: The material is prepared by the method for preparing a porous silicon negative electrode material coated with a gallium nitride carbon layer as described in any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: It includes the gallium nitride carbon layer coated porous silicon negative electrode material as described in claim 9.
